Short-Term Changes in Mental, Physical, and Social Factors After Metabolic Bariatric Surgery in Adolescents: A Nationwide Prospective Cohort Study - Goldenshluger, Ariela; Maor, Tamar; Via-Kagan, Renana; Zelekha, Orly; Gepner, Yftach (Frontiers in Nutrition, 2022)
Background Metabolic bariatric surgery (MBS) is an effective treatment for adolescents with severe obesity. However, changes in mental, physical, and social factors, as well as their association with the extent of excess weight loss (%EWL) after MBS, remain controversial. Methods We followed 97 adolescents (64% females, aged 17 ± 0.9 years, BMI 46.1 ± 5.9 kg/m2) before and 9 months following MBS in a multi-center, prospective cohort study. Changes in mental, physical, and social factors were assessed by self-reported questionnaires, and associations with %EWL were evaluated after adjustment for potential confounders. Results The body mass index (BMI) decreased by 30%, and all physical parameters significantly improved (p ≤ 0.001). Energy level increased by 24%, mood level by 14%, and mental health by 9.5% (p ≤ 0.002). Social parameters were also improved, with a significant decrease in social rejection (p = 0.02), and an increase in participation in after-school social activities (p = 0.008). Mental health improvement was associated with baseline social rejection (r = 0.514, p < 0.001). The improvement in all factors was not related to the extent of %EWL. Conclusion Metabolic bariatric surgery MBS in adolescents led to a meaningful decrease in BMI and to an improvement in short-term physical, mental, and social factors that were not related to %EWL. Patients experiencing social rejection may improve their mental health following BS.